2022
DOI: 10.1029/2022gl097802
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Intraseasonal Chlorophyll‐a Concentration in the Tropical Indian Ocean by the Central Indian Ocean Mode

Abstract: This study diagnoses the drivers of intraseasonal variability of mixed layer chlorophyll‐a (Chl) concentration in the tropical Indian Ocean during boreal summer (June–September) using a well‐tested coupled ocean‐ecosystem model. Results show that wind forcing is the primary source for energetic intraseasonal Chl concentration variability in the eastern Arabian Sea and western Bay of Bengal (BoB) modulated by the Central Indian Ocean (CIO) mode. The atmospheric anomalous anticyclone associated with the positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Physical–biogeochemical models are useful tools for the analysis of the variability of subsurface Chl under the influence of physical processes such as upwelling, eddies, fronts and sub‐mesoscale currents (Gan et al., 2010; Guo et al., 2017; Lévy et al., 2018; Xiu & Chai, 2011). The fully coupled physical–ecosystem model developed by the Darwin project of the Massachusetts Institute of Technology (https://darwinproject.mit.edu) has been successful in modeling the key phytoplankton size classes and seasonal/intra‐seasonal variation of surface Chl (Qin et al., 2022) and has already been used by several research groups to study phytoplankton community structure (Benoiston et al., 2017; Kuhn et al., 2019; Mangolte et al., 2022). This well‐tested and eddy‐permitting model is useful for studying the impact of mesoscale eddies on SCM characteristics and phytoplankton community.…”
Section: Introductionmentioning
confidence: 99%
“…Physical–biogeochemical models are useful tools for the analysis of the variability of subsurface Chl under the influence of physical processes such as upwelling, eddies, fronts and sub‐mesoscale currents (Gan et al., 2010; Guo et al., 2017; Lévy et al., 2018; Xiu & Chai, 2011). The fully coupled physical–ecosystem model developed by the Darwin project of the Massachusetts Institute of Technology (https://darwinproject.mit.edu) has been successful in modeling the key phytoplankton size classes and seasonal/intra‐seasonal variation of surface Chl (Qin et al., 2022) and has already been used by several research groups to study phytoplankton community structure (Benoiston et al., 2017; Kuhn et al., 2019; Mangolte et al., 2022). This well‐tested and eddy‐permitting model is useful for studying the impact of mesoscale eddies on SCM characteristics and phytoplankton community.…”
Section: Introductionmentioning
confidence: 99%
“…Determining MISO trends is thus critically important for understanding future changes in the spatial pattern of ISM. Meanwhile, it was widely reported that MISO has a large influence on extreme weather and climate events (Kikuchi & Wang, 2010; Li et al., 2013, 2020; Qin et al., 2022; Singh et al., 2014; Vinnarasi & Dhanya, 2016). Our results aid the understanding of potential contributions to extreme events from the perspective of intraseasonal variability during ISM.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional water quality monitoring method based on field investigation, remote sensing technology has the advantages of a low cost, wide range and high efficiency. With the development of highresolution and multi-source satellite sensors, the retrieval of water-environment-related elements using remote sensing has been widely applied in the monitoring of water quality and hydro-environmental pollution in large areas of water [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%